Asset Management Competencies and Organizational Structure on the Effectiveness of Village Asset Management - Rachmawati, Rima; Mulyawan, Ferry; Gunanta, Remon; Nababan, Daniel (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the effect of asset management competence with the effectiveness of village asset management. The research was conducted on the existing village in the city of Bandung with the technique of purposive sampling. The result of this research concludes that asset management competence influence the effectiveness of asset management of village with the variability of effectivity of asset management of village formed by competence of asset management equal to 27,9% and increase after organizational structure as variable the moderate both competence relation to effectively of asset management of village. Description analysis concludes that there are still obstacles in managing village assets such as that there is no accurate recording and documentation of assets so that they are controlled by other parties because the low proof of ownership and report does not reflect accountability. It is that causes Audit Board of the Republic of Indonesia to provide a Fair Exception Opinion.Â Â